Hubungan antara Linguistic Intelligence terhadap Self-Confident Siswa - Didik Kurniawan; Muhimmatul Hasanah (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2022)
In the process of human education, intelligence has been owned and must be developed. One of the intelligence possessed by humans is linguistic intelligence. Linguistic intelligence is the ability possessed by a person to process words through writing, and expressions as a form of expressing his thoughts. In addition, one of the psychological factors that contribute to student success is self-confidence. In the study of self-confidence, the skills that must be mastered include speaking, listening, writing, and reading. This study aims to empirically prove whether there is a relationship between linguistic intelligence and self-confident students at MA Tarbiyatus Shibyan Sidorejo Panceng Gresik. This research approach uses quantitative research with the type of correlation research. The research subjects were 69—the data collection method used linguistic intelligence and student self-confident questionnaires. The data analysis technique used is the correlation test. The results showed that: There is no relationship between linguistic intelligence and self-confident MA Tarbiyatus Shibyan Sidorejo Panceng Gresik students. This is based on calculations using the person correlation test, the value of Sig. (2-tailed) = 0.044 > 0.05. Because of the value of sig. (2-tailed) is greater than the probability value. The level of linguistic intelligence is in the Medium category, with a minimum score of 51 and a maximum value of 92. As for the level of self-confidence obtained, namely: High with a minimum value of 88 and a maximum value of 148.